The Impact of EESG Dimensions on Market Valuation of Firms Within Publicly-listed Logistics and Transportation Sector in Indonesia - Maulana, Aiden Awal (CV. Syntax Corporation Indonesia, 2025)
Indonesian companies are becoming more pressured to schedule, budget, and release sustainability reports, including for companies in the Indonesian logistics and transportation industry. Unfortunately, little empirical evidence exists about the financial value of filing of sustainability reports in emerging markets. The purpose of this research is to investigate the relationship between the contents of sustainability reports and the financial performance of publicly-listed logistics and transportation companies listed on the Indonesian Stock Exchange (IDX) for the period 2019-2024. This study, utilizing a revised EESG (Economic, Environmental, Social, Governance) evaluation framework, examines the content of sustainability reports. This analysis applied multiple linear regression (MLR) to consider effects on firms’ Tobin’s Q (TQ). Results indicated that, except for the partial significance of the Environmental dimension, other dimensions did not significantly affect market valuation. The findings indicate that sustainability reporting within this industry may emphasize requirements disclosure and environmental disclosure for value addition.